Effect of varying the density of Ag nanowire networks on their reliability during bending fatigue. (1st March 2019) - Park, Minkyu; Kim, Wonsik; Hwang, Byungil; Han, Seung Min
Abstract: The effect of varying the density of Ag nanowire networks on their reliability was explored during cyclic bending. The reliability of the Ag nanowire network was degraded as the density of nanowires decreased, which is in contrast to E-beam evaporated dense Cu thin films that showed enhanced reliability for thinner films. The cause for such a reverse trend is explained by a percolation mechanism considering that the failure in the Ag nanowire network occurs locally at the junctions that are randomly distributed as opposed to fatigue-induced channel crack formation in a Cu thin film. Graphical abstract: